Answer:
Step-by-step explanation:
2g + h = 2 --------------(I)
g - h = -5------------(II)
g = -5 + h
Plugin g = -5 + h in equation (I)
2(-5 + h) + h = 2 {Distributive property:a(b+c) = a*b +a*c}
(-5)*2 + h *2 + h= 2
-10 + 2h + h = 2
3h = 2 + 10
3h = 12
h = 12/3
h = 4
Substitute h= 6 in equation (I)
2g + 4 = 2
2g = 2 - 4
2g = -2
g = -2/2
g = -1
Answer:
see on assitant of press your middle button
The correct answer is 67 ur welcome
Cramer's Rule is a method that uses determinants to solve systems of equations that have the same number of equations as variables
Answer:
B
Step-by-step explanation:
The closed circle at - indicates that x can equal this value
The open circle at indicates that x cannot equal this value.
All values of x between - and are valid, thus
- ≤ x < → B